An immobilised Grubbs 2nd generation catalyst for application in flow-through devices - Gmeiner, Julia Renate; Leopold, Max; Lang, Carolin; Gaertner, Ute; Trapp, Oliver (Advanced synthesis & catalysis, 2014)
An improved immobilised Grubbs 2nd generation catalyst and its application in flow-through devices, shown for on-column reaction gas chromatography (ocRGC), has been studied. The coupling of a reaction capillary and a separation column in GC/MS allows direct reaction monitoring and analysis of conversion as well as reaction kinetics. The presented permanently bonded N-heterocyclic carbene ligand shows a great stability and activity in ring closing metathesis reactions. A salt-free approach was used to generate the carbene ligand, which can be directly monitored by mass spectrometry. The very flexible design of the immobilised ligand system in reaction channels and capillaries of flow through systems allows the preparation of various catalysts using a broad variety of metal precursors. This strategy of immobilised catalytically active complexes offers a wide range of on-column reactions combinable with fast reaction screening by high throughput experimentation.
Gesehen am 10.08.2020